(untitled) - Iram Iqbal; Dr. Zainab Amin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Stress is a natural psychological and physiological response to the demands of everyday life. Feeling overwhelmed by mental or emotional stress can turn into stress when you feel out of control. While a certain level of stress may motivate one person, the same level of stress may depress another. When you’re under a lot of stress, your body’s defense system, called "fight or flight," kicks in. Human has been created as a mixture of two basic essential parts i.e. soul and body, of which the spiritual aspect is of great importance in human life, through which man is connected with his creator and owner and he By knowing Him, one strives to become His perfect servant - If a person knows his Creator and lives his life according to the will of Allah, such a person will not be overwhelmed by fear, anxiety and depression - if he were to neglect it. And if he does not fulfill the purpose of his master by utilizing the requirements of the soul, then he will be subject to inner restlessness, anxiety and conflict, which may result in mental stress, as Allah says: "Those who follow my guidance will have no fear, nor will they grieve." This mental tension usually increases due to intolerance, so much so that it has recently swallowed nine lives in a single household in Pakistan Malakand Division. Conflicts can be seen everywhere nowadays. You can see its scenes from the riots of your neighborhood to national, regional and international riots. Our test in this age is what attitude we choose. Lest we be among the instigators of riots by importing or exporting them and suffer the punishment for the atrocities of others. In this article, the negative effects of mental stress and the role of Islamic law in its solution have been discussed.